The 2023 Flight of the Faint Intergalactic-medium Redshifted Emission Balloon - Drew M. Miles; Vincent Picouet; Zeren Lin; Ignacio Cevallos-Aleman; David Schiminovich; Nicolas Bray; Charles-Antoine Chevrier; Greyson Davis; Erika Hamden; Keri Hoadley; D. Christopher Martin; Bruno Milliard; et al. (The Astrophysical Journal Supplement Series)
The second iteration of the Faint Intergalactic-medium Redshifted Emission Balloon (FIREBall-2) is a UV multiobject spectrograph designed to detect emission from the circumgalactic and circumquasar medium at low redshifts ( z < 1). The FIREBall-2 instrument uses a zero-pressure suborbital balloon to access a stratospheric transmission window centered around 205 nm. Following the payload’s first flight in 2018, several refurbishments and modifications were made to the instrument and telescope to prepare for additional flight opportunities. Here we present an overview of upgrades and improvements made since the previous flight and discuss the 2023 field campaign, which culminated in a flight from Fort Sumner, New Mexico, in 2023 September. The flight was terminated early, prior to science observations; we report here the performance of the instrument in ground calibrations, the flight plan and timeline of events, and the in-flight guidance performance. We also discuss the limitations encountered in 2023 and the future outlook for FIREBall-2.